Cloud stabilization and storage stability of hot pepper sauce - Afroilan, Loida Adelaida Fontejon
The study was undertaken with the main objective of finding a process that would prevent the separation of components of hot pepper sauce and establishing the storage stability of the product at refrigerated (8-12°C), ambient (28-32°C), and accelerated (32-38°C) temperatures. In phase I, mixing or homogenizing alone was not sufficient to stabilize samples of hot pepper sauce. A combination of both processes was needed to produce a stable cloud. In phase II, the proper homogenizing and mixing procedures were established. It was found through objective and sensory tests that the procedure of running the hot pepper sauce in a colloidal mill thrice and mixing the solution in an osterizer for 10 minutes produced a stable solution even after the storage time pf 7 days. The viscosity of the hot pepper sauce increased and cloud separation was prevented. A storage temperature of 8-12°C was found to be the best storage condition as it kept the hot pepper sauce homogeneous even after four weeks of storage. This temperature also prevented the discoloration and decrease in the consistency of the sauce. The pungency of the hot pepper sauce was not greatly affected even under ambient and accelerated temperatures. The attributes greatly affected by ambient and accelerated temperatures were viscosity and color. The pH level and soluble solids content of all three samples were fairly stable throughout the four weeks of storage stu